Analytical-Behavioral Family Therapy for Anorexia Nervosa in adolescence: case study - Alckmin-Carvalho, Felipe; Melo, Márcia Helena da Silva (Perspectivas em Análise do Comportamento, 2022)
The aim of this study was to present the process and results of family behavior analytic therapy for the treatment of a 12 years old teenager patient with Anorexia Nervosa (AN). The process of psychotherapy lasted six months. There were 25 sessions with the teenager and her parents. The treatment involved the construction of functional analyzes to identify and manage the determinants of behaviors with the function of losing weight, psychoeducation, self-monitoring, systematic desensitization, clarification of rules associated with body and eating, bibliotherapy and socio-emotional and educational skills training. Instruments used at the beginning, at the end of treatment and at follow-up: anthropometric assessment, Eating Disorder Examination Questionnaire, to assess the severity of eating disorder and Youth Self-Report, to assess emotional/behavioral problems. The patient started treatment with low weight and amenorrheic. At the end of the treatment, she was eutrophic and with regular menstruation. She remained eutrophic and had regular menstrual status at follow-up. Both the AN severity and the indicators of emotional/behavioral problems were reduced post-intervention, and a further reduction was observed at follow-up. There is indication that the treatment may have positive effects, both in terms of weight recovery and in terms of eating psychopathology and other associated problems